Haze is a risk factor contributing to the rapid spread of respiratory syncytial virus in children - Ye, Qing; Fu, Jun-fen; Mao, Jian-hua; Shang, Shi-qiang (Environmental science and pollution research international, 2016)
This study investigated whether respiratory syncytial virus (RSV) infection in children was associated with ambient temperature and air pollutants in Hangzhou, China. A distributed lag non-linear model (DLNM) was used to estimate the effects of daily meteorological data and air pollutants on the incidence of RSV infection among children. A total of 3650 childhood RSV infection cases were included in the study. The highest air pollutant concentrations were in January to May and October to December during the year. The yearly RSV-positive rate was 10.0 % among children with an average age of 4.3 months. The highest RSV-positive rate occurred among patients 0 to 3 months old. Children under 6.5 months old accounted for 80 % of the total patients infected by RSV. A negative correlation was found between ambient temperature and RSV infection, and it was strongest with minimum ambient temperature ( r = −0.804, P < 0.001). There was a positive correlation between the infection rate and the particulate matter (PM) 2.5 ( r = 0.446, P < 0.001), PM10 ( r = 0.397, P < 0.001), SO 2 ( r = 0.389, P < 0.001), NO 2 ( r = 0.365, P < 0.001) and CO ( r = 0.532, P < 0.001). The current study suggested that temperature was an important factor associated with RSV infection among children in Hangzhou. Air pollutants significantly increased the risk of RSV infection with dosage, lag and cumulative effects.